Seismic Interpretation of Basement Faults Using Seismic Attributes: Using a Case Study of the Anding Field - Lim , Sook Fun (Universiti Teknologi PETRONAS, 2014)
Fractured basements have been extensively explored recently since the major discovery of oil in the fractured granite basement of Cuu Long Basin in Vietnam offshore area. Thus, further studies and exploration efforts have been employed for the Malay Basin whose basement lithology vary from metasediments, to volcanics, granites, and carbonates which clearly lack in primary porosity. However, the fractures that characterise the basement might contribute to secondary porosity; thus, enabling the basement to be a potential reservoir. The fractured basement actually does fit the criteria of a petroleum system, as in having a seal, an external source rock, and a sealed reservoir with secondary porosity. The matrix becomes the major oil storage, while the open fractures become the oil flow conduit. As faults are highly associated to fracture zone, delineating and characterising the faults is a step forward in further assessing the fracture network. Since faults are easily identified in 3D seismic data, further interpretation on the fault zone will help characterise the surrounding fracture network. Thus, characterisation of the fault zones is the most vital process prior to locating fractures. A fault characterisation workflow has been derived to enhance these faults on the seismic volume where parameterization of the attributes will also be applied. Application of a collection of attributes and parameterisation of these attributes will help confirm the location of the fault zones plus enhancing its visibility.